Pengaruh Stimulasi Assisted Crawling Terhadap Kemampuan Merangkak Bayi di Puskesmas BP Nauli Kec. Siantar Marihat Kota Pematangsiantar Tahun 2023 - Besty Agustina Silitonga; Asnita Sinaga; Isyos Sari Sembiring; Indra Agussamad (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Growth and development disorders are a problem that is often found in society, so it is very important that all components involved in children's growth and development, namely parents, teachers and the community, can work together in early monitoring. The determining factors for the quality of a child's growth and development are constitutional genetic-heredo potential (intrinsic) and the role of the environment (extrinsic). Child growth and development disorders occur when there are genetic factors and/or environmental factors that are unable to meet the child's basic growth and development needs. Factors that influence a child's growth and development are genetic factors, and are more influenced by environmental factors and the diseases experienced by the child. Appropriate detection and intervention can optimize the quality of the child's subsequent growth and development. Babies who experience delays in development will make the baby's parents feel anxious and worried, which will affect how parents meet their baby's needs, such as mothers who do not encourage their babies to talk and mothers who do not exercise their hands and feet regularly at certain times. So that the baby has difficulty walking and lacks language, the lack of stimulation given to the baby will worsen the baby's developmental delays (Hurlock, 2002).Based on a preliminary survey conducted at the BP Nauli Community Health Center on 10 mothers who had babies, there were 5 mothers who did not provide stimulation to their children when their children were not going through the crawling phase and did not know the effect on the child's development, so based on these problems the researchers wanted to conduct research with the title